ANALYSIS OF STRATEGIES IN FACING BUSINESS COMPETITION AND PRICING FOR CUSTOMER SATISFACTION AT BOUTIQUE ROSSY, BERBEK, NGANJUK - Istan Wighara Moelyono (Sean Institute, 2023)
In this era of globalization, business competition is inevitable as a result of which competition arises in offering quality products at prices that are able to compete in the market, and good service. Business is one of the pillars of the economy in this life. The current phenomenon that attracts the rampant development of shops. At